The Academic Profession as Perceived by Faculty - Elena Kochukhova (Voprosy obrazovaniya / Educational Studies Moscow, 2020)
This paper analyzes the findings from a study of faculty’s perceptions of teaching as the most significant component of the academic profession. In a broader context, it investigates into the transformation of the academic profession, meaning that professors in Russia as well as around the world tend to perform research, administrative, and expert functions more and more often. Previously, Russian researchers observed a conflict between faculty’s perception of teaching as the most important profession component and administrators’ publication productivity requirements. A number of publications present strategies that professors use to adjust to the changing administrative requirements. However, the existing findings mostly reflect administrators’ perception of the academic profession, on which the faculty’s perspective is considered to be implicitly dependent. Available literature offers little evidence of how professors perceive the content, meaning, and goals of the academic profession. The present study was designed to find out by which goals and norms faculty members are guided in doing their work and to determine the logic behind the way they allocate their efforts among various aspects of teaching. Data was collected using focused in-depth interviews carried out in a Yekaterinburg university. Research was performed within a methodological framework of grounded theory and narrative analysis which traces its origin to hermeneutics. Findings indicate that professors share similar perceptions of the skills necessary to do their work, the goals of teaching, and the criteria for maintaining educational quality. Meanwhile, there is no platform for building those perceptions, faculty’s attitudes being shaped under the influence of their mentors and personal experience. The study also evaluates the impact of other university actors (students, colleagues, administrators) on the respondents’ perceptions of the teaching process. Finally, a rationale for building professional solidarity within the university’s academic community is provided.